2020
DOI: 10.3390/v12080885
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Ionizing Radiation Induces Selective Killing of HIV-1-Infected Cells with Reversal of Cytokine Induction Using mTOR Inhibitors

Abstract: HIV-1 infects 39.5 million people worldwide, and cART is effective in preventing viral spread by reducing HIV-1 plasma viral loads to undetectable levels. However, viral reservoirs persist by mechanisms, including the inhibition of autophagy by HIV-1 proteins (i.e., Nef and Tat). HIV-1 reservoirs can be targeted by the “shock and kill” strategy, which utilizes latency-reversing agents (LRAs) to activate latent proviruses and immunotarget the virus-producing cells. Yet, limitations include reduced LRA permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 169 publications
(272 reference statements)
0
8
0
Order By: Relevance
“…When the relationship between CBD and autophagy was investigated using a biotinylated-CBD pull-down from U1 monocytes and monocyte-derived macrophages for spectrometry analysis, Reactome pathway enrichment analysis showed significant enrichment of proteins in Reactome autophagy pathways (Macrophage: R-HSA-9663891, R-HSA-1236974, R-HSA-1632852, R-HSA-9612973; Monocyte: R-HSA-9646399, R-HSA-9663891, R-HSA-9612973, R-HSA-1632852, R-HSA-9613829, Supplementary Figure S14 ). Our lab recently published a study demonstrating the reduction of latency-reversing agent (LRA)-mediated production of proinflammatory EVs released from HIV-1 infected cells by two autophagy inducers, rapamycin and INK128, exhibiting a correlation between inflammation and autophagy [ 98 ]. Furthermore, other studies showed that HIV-1-mediated autophagy deregulation was shown in neurons and dendritic cells, with increased secretory autophagosomes shown in HAND patients exhibiting encephalitis [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the relationship between CBD and autophagy was investigated using a biotinylated-CBD pull-down from U1 monocytes and monocyte-derived macrophages for spectrometry analysis, Reactome pathway enrichment analysis showed significant enrichment of proteins in Reactome autophagy pathways (Macrophage: R-HSA-9663891, R-HSA-1236974, R-HSA-1632852, R-HSA-9612973; Monocyte: R-HSA-9646399, R-HSA-9663891, R-HSA-9612973, R-HSA-1632852, R-HSA-9613829, Supplementary Figure S14 ). Our lab recently published a study demonstrating the reduction of latency-reversing agent (LRA)-mediated production of proinflammatory EVs released from HIV-1 infected cells by two autophagy inducers, rapamycin and INK128, exhibiting a correlation between inflammation and autophagy [ 98 ]. Furthermore, other studies showed that HIV-1-mediated autophagy deregulation was shown in neurons and dendritic cells, with increased secretory autophagosomes shown in HAND patients exhibiting encephalitis [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Background low levels of apoptosis could also be responsible for the presence of several cellular proteins in 2 k EVs. However, we expect that these apoptotic vesicles are not derived from dying cells [ 35 , 56 ]. These findings revealed the possibility that HTLV-1 EVs may also carry important cytokines and chemokines with the potential to further regulate the immune system of an infected host.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we recently observed that HIV-1 in PBMCs may modulate packaging of viral proteins and inflammatory cytokines into EVs, depending on the transcriptional status of the virus. These resulting EVs were able to cause inflammation in HLM-1 indicator-indicator recipient cells, as evidenced by the release of TNF-α and viral activation [ 246 ]. These data reveal the importance to clarify blood and plasma samples from EVs and to consider EVs as a biomarker of disease severity, in particular because of the potential EV-mediate effects reported that may contribute to disease severity.…”
Section: Strategies For Preventing the Viral Transmissionmentioning
confidence: 99%